Penerapan Sistem Pelayanan Informasi Publik terhadap Kepuasan Masyarakat Kota Tangerang - Sanjaya, Hani; Hilman, Hilman; Mayza, Thita Moralitha (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research analyzes the implementation of the public information service system at the Public Information and Documentation Center (PPID) of Tangerang City with the aim of enhancing public satisfaction. The method used is qualitative, supplemented with quantitative data through interviews, observations, and literature reviews. Data analysis techniques use the calculation of the Community Satisfaction Index (CSI) by using the weighted average value of each service element. The research findings indicate that the PPID of Tangerang City provides two channels for information requests: face-to-face and online through the website and email. The verification of requirements takes 3 working days, with information provided within 10 working days if the requirements are complete. The PPID of Tangerang City also improves accessibility with a disability-friendly website and Braille forms. The legal basis for the PPID of Tangerang City is the Public Information Disclosure Law No. 14 of 2008. Socialization is carried out through campus cooperation and Instagram but is limited to internal teams due to low information requests. The PPID of Tangerang City provides facilities and infrastructure in accordance with regulations and improves employee performance through training. This research provides an in-depth understanding of the implementation of the public information service system at the PPID of Tangerang City and serves as a basis for improvement to enhance public satisfaction.